Discrimination of Different Parts of Saffron by Metabolomic‐Based Ultra‐Performance Liquid Chromatography Coupled with High‐Definition Mass Spectrometry. Issue 10 (4th September 2019) - Xu, Shuya; Ge, Xiaojin; Li, Shimin; Guo, Xiaoyang; Dai, Dandan; Yang, Tiegang
Abstract: In this study, the metabolite profiling of three different parts of Crocus sativus L. was measured by using ultra‐performance liquid chromatography‐quadrupole time‐of‐flight mass spectrometry (UPLC‐QTof‐MS/MS). Multivariate statistical analysis was used to distinguish among the samples from different parts. A total of 54 compounds were identified in tepals, stigmas and stamens by UPLC‐QTof‐MS/MS. The results stated that chemical characteristics of saffron were obviously diverse in terms of the parts of flower. Through analysis, coniferin and crocin‐2 were special components in stigmas when compared to tepals and stamens. The content of flavonoids was high in tepals when compared with the stigmas. The tepal of saffron may processed as a source of flavonoids in the future. The research provided the basis for the theory that only the stigma can be used as medicine. Abstract :